Ensino fundamental de nove anos : para além do ajuste legal - Fortunato, Raquel Paula (2014)
The objective of this research is analyze the extent of implementation of Law n. 11.274/2006, which established the obligation of the nine-year basic education, has founded a new pedagogical organization, with the aim of greater democratization of education, of universalization of access and citizen s basic education. The study takes as its point of departure the historical comprehension of the social right to education in Brazil, its obligation and the expansion of school permanence time. Based on the documental analysis, research unveils the 11.274/2006 law intricacies, offering special attention to the publications related to its application, derived from the Ministry of Education. Having as reference the analysis of documents (school regulations, curricula and political-pedagogical project) of two municipal schools, two state and one private school in the city of Passo Fundo, and semistructured interviews, with directors and coordinators of schools and their respective maintainers, It is observed the implementation process of this law in the movement it caused inside these institutions. The theoretical framework of this investigation encompasses Sonia Kramer studies on childhood, José Gimeno Sacristan's about the curriculum and Ilma Steps Veiga's on political-pedagogical project, among other authors. The analysis resulting from the methodological triangulation of data and from the synoptic frame of contents, organized by categories, allow to highlight that the educational policy of the country, over the years, have been implementing important measures to democratize education, expand and ensure students staying in school, in order that they conclude primary school. The alluded law was implemented in the city of Passo Fundo in a very heterogeneous way. The studied schools were able to partially attend the construction of a new logic of school organization, because some limitations, among which the absence of a pact arount the major educational issues that the Law provides, have prevented them from obtain more satisfactory results